Optimization of the spectroscopic method using potassium peroxymonosulfate for determination of antioxidant capacity - Marjanović, Aleksandra; Đeđibegović, Jasmina; Popovac, Sanida; Omeragić, Elma; Korać, Fehim; Čaklovica, Faruk; Turalić, Amila; Šober, Miroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
In this study, we were testing possible usage of commercial tablets for dental prosthesis, containing potassium peroxymonosulfate as a reagent for determination of antioxidant capacity in vitro. Our aim was to develop fast, simple and cheap method for determination of antioxidant capacity that will be suitable for laboratories with modest resources. This method was previously proposed, but we have chosen somewhat different approach. Because of the quite narrow linear range, when ascorbic acid was used as standard, for the preparation of the calibration curve, we have used a catechin in the concentration range from 0.125 mg/mL to 12.5 mg/mL. Obtained calibration curve was linear with correlation coefficient of R2=0.992 and it was used for further determination of antioxidant capacity of selected samples. In order to test the possibility of this method for determination of antioxidant capacity of real samples, we have used five samples which antioxidant capacity was proven in previous testing with different in vitro and in vivo methods.